Effects of in-season uphill sprinting on physical characteristics in semi-professional soccer players - Kavaliauskas, M.; Kilvington, R.; Babraj, J. (The Journal of Sports Medicine and Physical Fitness, 2017)
Background: Soccer performance is determined by a number of physiological adaptations that can be altered by high intensity training. However, the effectiveness of using an uphill sprint based protocol has not been demonstrated for soccer players. We sought to determine the effectiveness of an in-season uphill sprint training (UST) programme on soccer related physiological outcomes.